Non-linguistic teaching behaviors in English language teaching: A systematic mapping review of measures and reported outcomes - Danny Dermawansyah; Tryanti R. Abdulrahman (Universitas Islam Negeri Ar-Raniry, 2026)
This systematic mapping review synthesizes 44 empirical studies published between 2010 and 2025 to examine how nonlinguistic teaching behaviors—increasingly relied upon in English language teaching (ELT) to guide attention, support meaning-making, and shape classroom interaction—are defined, operationalized, and linked to reported outcomes in ELT settings. Seven behavioral categories emerge from the evidence base: kinesics, oculesics, proxemics, haptics, paralinguistics, chronemics, and appearance or artifacts. These behaviors are measured using observation-based, perception-based, research-driven, and technology-assisted methods, resulting in a multimodal corpus that nonetheless exhibits a strong weighting toward kinesic features. Reported associations cluster across three outcome domains: classroom processes, student engagement, and perceived teacher effectiveness. However, outcome labels are frequently broad, and measurement granularity varies considerably, limiting analytical precision and cross-study comparability. The review identifies significant gaps in contextual coverage, construct alignment, and methodological consistency, indicating a field that is empirically active yet uneven in its development. To advance both theoretical rigor and instructional relevance, future research should establish clearer construct definitions, implement more robust multimodal measurement strategies, and adopt context-sensitive designs capable of elucidating the mechanisms through which nonlinguistic behaviors relate to learning-relevant processes.